Cloud Computing Impelementation Using Model Roadmap for Cloud Computing Adoption (ROCCA) on IT Consultant Industry - Panji Arief Perdana; Suharjito Suharjito (Bina Nusantara University, 2017)
The purpose of this research was to build cloud computing referring to Roadmap for Cloud Computing Adoption (ROCCA) model so that the best strategy could be implemented in PT Matrica Consulting Service. The implementation of cloud computing had five stages modifications ROCCA adoption model. Those stages were analysis, design, adoption, migration, and management. Data were taken from distributing questionnaires and conducted interviews with R&D Manager and analyzed using SWOT analysis. The result is the implementation of cloud computing models, and implementation of private cloud and Software as a Service (SaaS) needs to be modified so it can be implemented properly. The implementation canincrease the performance PT Matrica Consulting Service based on the characteristics of the cloud which is flexible and secure to be accessed as long as it is connected to the Internet and maintained properly.